2005
DOI: 10.1111/j.1368-5031.2005.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and seizures: emphasis on newer agents and clinical implications

Abstract: Seizures are a known, relatively rare, consequence of antidepressant treatment. Risk estimates vary depending on the study, source of data and patient population, predisposed vs. nonpredisposed. For newer antidepressants (e.g. selective serotonin reuptake inhibitors, bupropion, mirtazepine, etc.), the risk is generally considered to be low (0.0%-0.4%) and not very different from the incidence of first seizure in the general population (0.07%-0.09%). Risk with tricyclic antidepressants at effective therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 33 publications
2
65
1
3
Order By: Relevance
“…In animal studies using atomoxetine or reboxetine, convulsions were observed only at extremely high doses (Wong et al, 2000;Wernicke et al, 2007). The incidence of seizures during treatment with NRIs has been reportedly rare (Montgomery, 2005;Wernicke et al, 2007). Brain levels of the drugs in overdose cases may be considerably higher than levels during treatment at therapeutic doses (Poggesi et al, 2000;Kiyono et al, 2004Kiyono et al, , 2008Garside et al, 2006;Kanegawa et al, 2006), suggesting that potent inhibition of neuronal GIRK channels by atomoxetine and reboxetine after overdose may contribute to increased seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies using atomoxetine or reboxetine, convulsions were observed only at extremely high doses (Wong et al, 2000;Wernicke et al, 2007). The incidence of seizures during treatment with NRIs has been reportedly rare (Montgomery, 2005;Wernicke et al, 2007). Brain levels of the drugs in overdose cases may be considerably higher than levels during treatment at therapeutic doses (Poggesi et al, 2000;Kiyono et al, 2004Kiyono et al, , 2008Garside et al, 2006;Kanegawa et al, 2006), suggesting that potent inhibition of neuronal GIRK channels by atomoxetine and reboxetine after overdose may contribute to increased seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since then drugs such as the SSRIs have been prescribed in increasing quantity, in part because of a lower risk of seizures both in normal use and after overdose (Montgomery, 2005). In turn they have featured more prominently in fatal poisoning data (Table 2).…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…35 There is also some evidence from animal models that during adolescence susceptibility to seizures is increased 36,37 and reported annual incidence rates of epilepsy are higher in patients of 10-19 years of age than in adults. 38 Ingested dose and probability of seizures Dose-dependency of occurrence of seizures is well-known in cases of drug overdose 34 venlafaxine. 19 The results in the literature and of our study support the mechanistic view of the pathophysiology of seizures in overdose which are thought to be provoked by overexcitation of the brain by different pathways in a dose-dependent manner.…”
Section: 3034mentioning
confidence: 99%